INDIAN ARCHAEOLOGY AFTER INDEPENDENCE - Ray, Himanshu Prabha. Link ([S.l.])
1 online resource
Keywords: The book presents the challenges faced by the Archaeological Survey of India (ASI) in the first two and a half decades after Indian independence. It looks at the shifts in Government policies, how ASI found its feet in a global environment, and the new realities of economic development such as big dam constructions that invariably resulted in the submergence of archaeological sites. Based on unpublished archival data, this book highlights the contributions of the longest-serving Director-General Amalananda Ghosh and members of his staff. It thus provides a corrective to the histories of archaeology that describe the policies of the post-1947 ASI as a continuation of colonial archaeologists such as Mortimer Wheeler, who was appointed Director-General at the cusp of Indian independence in 1944 by the British.The book will be indispensable to researchers and scholars of history, heritage studies and archaeology, and South Asian studies. It will also be of appeal to those interested in the history of archaeology and the development of the discipline in India.